(untitled) (Al-Qamar, 2024)
“Many distinguished scholars of Iqbal who have significantly contributed to the study and dissemination of his philosophy worldwide were Afghan diplomats affiliated with the Ministry of Foreign Affairs of Afghanistan. These ambassadors, through both poetry and prose in various languages, played an essential role in promoting Iqbal’s ideology. The intellectual depth and scholarly dedication exhibited by these ambassadors reflect a direct and profound connection with Iqbal’s philosophy. This intellectual legacy remains a valuable resource in contemporary times, offering insights for strengthening diplomatic and cultural relations between Islamic nations” Although my Ph.D. research focuses on "An Evolutionary Review of Iqbal Studies in Afghanistan," I found that Afghan ambassadors have played a continuous and influential role in the dissemination of Iqbal’s thought. There is a compelling need for further research on the contributions of these Afghan diplomats, as their efforts provide an invaluable intellectual resource for fostering diplomatic ties and promoting scholarly exchange among Islamic nations. Wherever these ambassadors were posted around the world, they continued to promote understanding and knowledge of Iqbal in their own languages. Below is a concise review of the global contributions of notable Afghan diplomats in the field of Iqbal studies.